2020
DOI: 10.1021/acsami.0c04577
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Stable All-Inorganic Niobium-Incorporated CsPbI2Br-Based Perovskite Solar Cells

Abstract: Inorganic cesium lead halide perovskite (CsPbX 3 ) is a promising lightharvesting material to increase the thermal stability and the device performance as compared to the organic−inorganic hybrid counterparts. However, the photoactive stability at ambient conditions is an unresolved issue. Here, we studied the influence of Nb 5+ ions' incorporation in the CsPbI 2 Br perovskite processed at ambient conditions. Our results exhibited that 0.5% Nb-incorporated CsPb 1−x Nb x I 2 Br (herein x = 0.005) thin films sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…b) The distribution of g ip E for all-inorganic perovskites. The data points are collected from relevant publications of CsPbI 3 , [25,26,[36][37][38][39][40][41] CsPbI 2 Br, [29,[42][43][44][45][46][47][48][49][50][51] CsPbIBr 2 , [30,[52][53][54][55][56][57] CsPbBr 3 , [58][59][60][61][62] of which detailed data can be found in Tables 1-5.…”
Section: Charge-carrier Mobilitiesmentioning
confidence: 99%
“…b) The distribution of g ip E for all-inorganic perovskites. The data points are collected from relevant publications of CsPbI 3 , [25,26,[36][37][38][39][40][41] CsPbI 2 Br, [29,[42][43][44][45][46][47][48][49][50][51] CsPbIBr 2 , [30,[52][53][54][55][56][57] CsPbBr 3 , [58][59][60][61][62] of which detailed data can be found in Tables 1-5.…”
Section: Charge-carrier Mobilitiesmentioning
confidence: 99%
“…FromFigure a, the EIS measurement was performed at an applied bias of 0.8 V in the dark environment. The equivalent circuit (EC) diagram was shown in the inset of Nyquist plots. , The fitting results are shown in Table S7. Compared with the devices fabricated without methanol solution (58.6 and 3743.4 Ω), the devices fabricated with 30 μL of CsBr methanol solution showed an increased R s of 65.5 Ω and a decreased R ct of 2559.8 Ω, while the devices fabricated with 90 μL of CsI methanol solution showed a decreased R s of 43.2 Ω and an increased R ct of 4554.9 Ω.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the Zn + cation can effectively improve the grain size and control the crystal growth of the CsPbI 2 Br film due to its stronger interaction with halide ions. [ 244 ] Yin and Patil et al [ 245 ] reported the positive influence of B‐site doping of Nb 5+ in improving the PV performance of CsPbI 2 Br. It was suggested that the 0.5% Nb‐incorporated perovskite film exhibited enlarged grain size and remarkable uniformity, delivering a superior interface between the HTL and the perovskite layer.…”
Section: Engineering Strategiesmentioning
confidence: 99%